Magnesium Bioresorbable Scaffold (BRS) Magmaris vs Biodegradable Polymer DES Ultimaster in NSTE-ACS Population—12-Month Clinical Outcome - Piotr Rola; Adrian Włodarczak; Szymon Włodarczak; Mateusz Barycki; Marek Szudrowicz; Magdalena Łanocha; Łukasz Furtan; Katarzyna Woźnica; Jan Jakub Kulczycki; Joanna Jaroszewska-Pozorska; Michalina Kędzierska; Adrian Doroszko; et al. (Journal of Interventional Cardiology, 2022)
Background. Percutaneous coronary intervention (PCI) in the acute coronary syndrome (ACS) setting is associated with a greater probability of device failure. The currently ongoing development of new scaffold technologies has concentrated an effort on improving the PCI outcomes, including the use of new biodegradable materials. This pilot study evaluates the performance of a magnesium bioresorbable scaffold (Magmaris, Biotronik, Germany) in comparison to the sirolimus‐eluting bioresorbable polymer stents (BP-SES) (Ultimaster, Terumo, Japan) in the NSTE-ACS setting. Methods. The population of this pilot comprised 362 patients assigned to one of two arms (193-Magmaris vs 169-Ultimaster). The data regarding the primary outcome comprised of death from cardiac causes, myocardial infarction, and stent thrombosis, along with target-lesion failure (TLF) and other clinical events was collected in the 1-yearfollow-up. Results. There were no statistically significant differences in clinical outcomes in the short term (30 days) or in the 1-yearfollow-up between both groups. Conclusion. At 12 months, there were no statistically significant differences between the Magmaris and Ultimaster for composed endpoints or the TLF.